Framing the Drivers of Antimicrobial Resistance in Tanzania - Anna Durrance-Bagale; Anne-Sophie Jung; Gasto Frumence; Leonard Mboera; Stephen E. Mshana; Calvin Sindato; Taane G. Clark; Mecky Matee; Helena Legido-Quigley (MDPI AG, 2021)
Despite global awareness of the key factors surrounding antimicrobial resistance (AMR), designing and implementing policies to address the critical issues around the drivers of AMR remains complex to put into practice. We identified prevalent narratives and framing used by epistemological communities involved in the response to AMR in Tanzania, interrogated how this framing may inform policymaking, and identified interventions that could be tailored to the groups believed responsible for AMR. We interviewed 114 key informants from three districts and analysed transcripts line by line. Our results suggest that many different groups help drive the spread of AMR in Tanzania and need to be involved in any effective response. Human health is currently perceived as driving the response, while other domains lag behind in their efforts. For AMR programmes to be successful, all sectors need to be involved, including civil society groups, community representatives, and those working in communities (e.g., primary care physicians). However, current plans and programmes largely fail to include these viewpoints. The perceived presence of political will in Tanzania is a significant step towards such a response. Any strategies to tackle AMR need to be tailored to the context-specific realities, taking into account constraints, beliefs, and power dynamics within countries.